Concentration levels, spatial variations and exchanges of polychlorinated biphenyls (PCBs) in ambient air, surface water and sediment in Bursa, Türkiye - Sari, Mehmet Ferhat; Esen, Fatma; Çetin, Banu (Elsevier B.V., 2023)
In this study, ambient air, surface water and sediment samples were simultaneously collected and analyzed for PCBs to investigate their levels, spatial variations and exchanges between these three compartments at different sampling sites for 12 months in Bursa, Türkiye. During the sampling period, a total of 41 PCB concentrations were determined in the ambient air, surface water (dissolved and particle phase) and sediment. Thus, 945.9 ± 491.6 pg/m3 (average ± STD), 53.8 ± 54.7 ng/L, 92.8 ± 59.3 ng/L and 71.4 ± 38.7 ng/g, respectively. The highest concentrations of PCBs in the ambient air and in water particulate phase were measured at the industrial/agricultural sampling site (1308.6 ± 252.1 pg/m3 and 168.7 ± 21.2 ng/L, respectively), ? 4–10 times higher than background sites; while the highest concentrations in the sediment and dissolved phase were measured at the urban/agricultural sampling sites (163.8 ± 27.0 ng/L and 145.7 ± 15.3 ng/g, respectively), ? 5–20 times higher than background sites. PCB transitions between ambient air-surface water (fA/fW) and surface water-sediment (fW/fS) were investigated by fugacity ratio calculations. According to the fugacity ratios obtained, volatilization from the surface water to the ambient air was observed at all sampling sites (98.7 % of fA/fW ratios are <1.0). Additionally, it has been determined that there is a transport from the surface water to the sediment (100.0 % of fW/fS ratios are higher than 1.0). The flux values in ambient air-surface water and surface water-sediment environments ranged from ?1.2 to 1770.6 pg/m2-day and from ?225.9 to 0.001 pg/m2-day, respectively. The highest flux values were measured for PCBs with low chlorine content (Mono-, Di-Cl PCBs), while the lowest flux values were measured for the high chlorine content PCBs (Octa-, Nona- and Deca-Cl PCBs). As it was determined in this study that surface waters contaminated by PCBs have the potential to pollute both air and sediments, it will be important to take measures to protect surface waters. © 2023 Elsevier B.V., All rights reserved.
Keywords: Bursa; Exchange; Passive air samplers; Spatial distribution; Temporal distribution